Spinal subarachnoid hematoma following lumbar puncture in a patient without coagulopathy: a case report - Kyung Ryeol Lee (Kosin Medical Journal)
Spinal subarachnoid hematoma (SSAH) following lumbar puncture (LP) in patients without coagulopathy is exceedingly rare, but can lead to severe neurologic complications, such as paraplegia. Although LP has been identified as a cause of SSAH in certain cases, its rarity underscores the need for a prompt diagnosis. Here, we present the case of a young patient who developed SSAH after LP and presented with headache and back pain. The patient was diagnosed accurately and rapidly using magnetic resonance imaging and was successfully managed with conservative treatment.